Menstrual hygiene management: a guide - Syed Hussien, Sh Fatimah Alzahrah (2021)
This presentation discusses on the issue of menstrual poverty and menstrual hygiene management in her chapter. Given that women make up almost half of the world population and approximately 800 women are menstruating monthly at any given time and do so for approximately 30 years of their lives, there needs to be more attention and care on the issue. Menstrual poverty or period poverty affects the lives of girls and women not only physically but also mentally, socially and their future outlook. The presentation further explains the different elements required for menstrual hygiene management and suggest a brief guide to address the issue of period poverty to start the conversation.